An ultra-high temperature self-limiting electric heat tracing band and a manufacturing method thereof
Patent Information
- Application Number
- CN202610859624.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-15
- Publication Date
- 2026-10-27
AI Technical Summary
[0002]自限温电伴热带利用正温度系数(PTC)材料的电阻自发调节特性,实现输出功率随温度升高而自动降低,广泛用于管道防冻、工艺伴热等领域,然而,现有产品在超过200℃的高温场景下,普遍存在PTC效应衰减、导电网络失稳、基体热氧化分解等问题,尤其在海上石油、核工业辅助管道、航空航天地面设备等高端领域,对伴热带的耐温性、耐腐蚀性及长期热稳定性提出了严苛要求
[0014]本发明提供的技术方案中,采用梯度辐照交联结构,表层高交联度提供了优异的抗热氧化和抗蠕变能力,芯层适度交联保留了PTC效应的稳定性,超声辅助分散确保了核-壳填料在基体中的均匀分布,显著延长了使用寿命,降低了维护更换成本;等离子体表面处理与原位聚合相结合制备核-壳结构导电填料,确保了填料结构的稳定性和可重复性;超声辅助熔融共混显著改善了填料分散均匀性,避免了传统机械搅拌导致的团聚缺陷;三层共挤一次成型实现了芯层、绝缘层、护套层的紧密结合,消除了层间界面缺陷。
Smart Images

Figure CN122994950A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrothermal application technology, specifically to an ultra-high temperature self-regulating electric heating cable and its manufacturing method. Background Technology
[0002] Self-regulating heating cables utilize the self-regulating resistance characteristics of positive temperature coefficient (PTC) materials to automatically reduce output power as temperature increases. They are widely used in pipeline antifreeze and process heat tracing. However, existing products generally suffer from problems such as PTC effect decay, conductive network instability, and thermal oxidation decomposition of the substrate in high-temperature scenarios exceeding 200°C. In particular, in high-end fields such as offshore oil, nuclear industry auxiliary pipelines, and aerospace ground equipment, stringent requirements are placed on the temperature resistance, corrosion resistance, and long-term thermal stability of the heating cables. Summary of the Invention
[0003] The purpose of this invention is to solve the above-mentioned problems by designing an ultra-high temperature self-regulating electric heating cable and its manufacturing method.
[0004] The first aspect of this invention provides an ultra-high temperature self-regulating electric heating cable and a method for manufacturing the same, wherein the ultra-high temperature self-regulating electric heating cable comprises a stranded nickel-plated copper conductor, a PTC heating core layer, a first insulating layer, a metal shielding layer, and an outer sheath layer; The manufacturing method of ultra-high temperature self-regulating electric heating tape includes the following steps: S1. Preparation of composite conductive filler: PFA resin, composite conductive filler, nucleating agent and antioxidant are melt-blended and ultrasonically dispersed to obtain PTC core material. S2. The PTC core material, the first insulation layer material, and the outer sheath material are co-extruded in one step through a three-layer co-extrusion die head to form a preform. S3. The preform is subjected to gradient irradiation crosslinking, and the irradiated product is annealed and polarized. A metal shielding layer is set on the outside of the formed composite and external terminals are installed to obtain an ultra-high temperature self-regulating electric heating cable.
[0005] Optionally, in a first implementation of the first aspect of the present invention, the PTC heating core layer adopts a PFA / hybrid carbon composite system, the conductive filler in the PFA / hybrid carbon composite system is a nanoparticle with a core-shell structure, and the PTC heating core layer exhibits a crosslinking degree gradient distribution along the radial direction, with the surface layer crosslinking degree being higher than that of the core layer, wherein the surface layer crosslinking degree is 85% to 95% and the core layer crosslinking degree is 60% to 75%.
[0006] Optionally, in a second implementation of the first aspect of the present invention, the shell of the nanoparticles is an in-situ polymerized conductive polymer layer, wherein the conductive polymer layer is a polydopamine layer or a conductive polyaniline layer, and the shell thickness is 5-15 nm.
[0007] Optionally, in a third implementation of the first aspect of the present invention, step S1 specifically includes the following process: S11. Select high-structure carbon black as the core material, place the carbon black in a plasma treatment chamber, and perform low-temperature plasma surface treatment under an oxygen or nitrogen atmosphere. The treatment power is 100-300W and the time is 5-15min. Introduce active groups on the surface of the carbon black, wherein the active groups are one of hydroxyl, carboxyl or amino groups. S12. Disperse the activated carbon black in a buffer solution containing dopamine or aniline monomers at a concentration of 2-10 g / L, and stir and polymerize at room temperature for 12-24 hours to form a conductive polymer shell. After polymerization, centrifuge, wash and vacuum dry to obtain a composite conductive filler with a core-shell structure. S13. Weigh the PFA resin, composite conductive filler, nucleating agent and antioxidant according to the weight parts, and put them into the mixer for premixing. Feed the premixed material into a twin-screw extruder. The blended melt is extruded through a die, cooled and granulated to obtain PTC core material particles.
[0008] Optionally, in the fourth implementation of the first aspect of the present invention, 60-80 parts of PFA resin, 15-25 parts of composite conductive filler, 5-10 parts of nucleating agent, and 1-3 parts of antioxidant are used.
[0009] Optionally, in the fifth implementation of the first aspect of the present invention, step S13 specifically includes the following process: PFA resin, composite conductive filler, nucleating agent and antioxidant are put into a mixer and premixed at room temperature for 5 to 10 minutes at a speed of 500 to 800 rpm to make the components initially dispersed evenly. The premixed material is fed into the twin-screw extruder through a metering feeder. The screw speed is 300-500 rpm. The temperature of each section of the twin-screw extruder is set as follows: feeding section 320-340℃, melting section 350-370℃, mixing section 370-380℃, and die head temperature 360-370℃. After the melting section of the twin-screw extruder, an ultrasonic probe is inserted into the material melt. The ultrasonic frequency is 20-40kHz and the power is 500-1000W. Under the action of ultrasound, the core-shell structure filler is uniformly dispersed. The blended melt is extruded through a die, cooled, and granulated to obtain PTC core material particles.
[0010] Optionally, in a sixth implementation of the first aspect of the present invention, step S2 specifically includes the following process: S21. A three-layer co-extrusion composite die head is used, and the inside of the die head adopts a split channel design so that the three layers of material converge in front of the exit die; The extruder temperature for the PTC core layer is 340–370℃, the extruder temperature for the first insulation layer is 350–380℃, the extruder temperature for the outer sheath layer is 350–380℃, and the co-extrusion die head temperature is 360–375℃. The extrusion speed of the PTC core layer extruder is 5-15 rpm, the extrusion speed of the first insulation layer extruder is 8-20 rpm, and the extrusion speed of the outer sheath layer extruder is 10-20 rpm. S22. The stranded nickel-plated copper conductor passes through the center of the die head at a constant speed of 1-5 m / min under the action of the traction device. The first insulation layer covers the outside of the PTC core layer, and the outer sheath layer covers the outermost layer. After extrusion, it is cooled and shaped by the sizing sleeve and cooling water tank to form a blank.
[0011] Optionally, in a seventh implementation of the first aspect of the present invention, the first insulating layer material is selected from PFA, which has high insulation resistance and high temperature resistance, and the outer sheath material is selected from PFA with added UV-resistant and corrosion-resistant additives.
[0012] Optionally, in the eighth implementation of the first aspect of the present invention, step S3 specifically includes the following process: S31. Unwind the obtained preform on an unwinding device and irradiate it through the electron accelerator irradiation chamber at a speed of 1-3 m / min for the first stage of irradiation. The electron beam energy is 1.5-3.0 MeV, the beam current intensity is 20-50 mA, and the irradiation dose is 80-120 kG. S32. The preform after the first stage of irradiation is sent into the second irradiation chamber. A cobalt-60 gamma ray source is used, and the irradiation dose is 30-60 kGy. By the difference in the irradiation dose between the two stages, a gradient distribution of crosslinking degree is achieved in the radial direction from the core layer to the surface layer. S33. The irradiated preform is placed in a nitrogen-protected oven. After the composite is cooled, tin-plated copper wire or nickel-plated copper wire is braided into a metal shielding layer using a braiding machine. S34. Remove the outer sheath and insulation layer at both ends of the heating cable to expose the conductor, and install explosion-proof and waterproof external terminals by welding to obtain an ultra-high temperature self-regulating heating cable.
[0013] Optionally, in a ninth implementation of the first aspect of the present invention, the oven is heated to 200°C at a rate of 5°C / min, held at that temperature for 1 hour, then heated to 240°C at a rate of 3°C / min, held at that temperature for 1 to 2 hours, and finally naturally cooled to below 60°C before being removed from the oven.
[0014] The technical solution provided by this invention employs a gradient irradiation crosslinking structure. The high degree of crosslinking in the surface layer provides excellent resistance to thermal oxidation and creep, while the moderate crosslinking in the core layer retains the stability of the PTC effect. Ultrasonic-assisted dispersion ensures the uniform distribution of the core-shell filler in the matrix, significantly extending its service life and reducing maintenance and replacement costs. The combination of plasma surface treatment and in-situ polymerization prepares the core-shell structure conductive filler, ensuring the stability and repeatability of the filler structure. Ultrasonic-assisted melt blending significantly improves the uniformity of filler dispersion and avoids agglomeration defects caused by traditional mechanical stirring. The three-layer co-extrusion one-time molding achieves a tight bond between the core layer, insulation layer, and sheath layer, eliminating interlayer interface defects. Attached Figure Description
[0015] Various other advantages and benefits will become apparent to those skilled in the art upon reading the following detailed description of preferred embodiments. The accompanying drawings are for illustrative purposes only and are not intended to limit the invention.
[0016] Figure 1 A flowchart of the manufacturing method of ultra-high temperature self-regulating electric heating cable provided in the embodiments of the present invention; Figure 2 A flowchart of step S1 provided in an embodiment of the present invention; Figure 3 A flowchart of step S2 provided in an embodiment of the present invention; Figure 4 A flowchart of step S3 provided in an embodiment of the present invention. Detailed Implementation
[0017] The terms “first,” “second,” “third,” “fourth,” etc. (if present) in the specification, claims, and accompanying drawings of this invention are used to distinguish similar objects and are not necessarily used to describe a particular order or sequence. It should be understood that such data can be interchanged where appropriate so that the embodiments described herein can be implemented in orders other than those illustrated or described herein. Furthermore, the terms “comprising” or “having,” and any variations thereof, are intended to cover a non-exclusive inclusion; for example, a process, method, apparatus, product, or device that comprises a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to such processes, methods, products, or devices.
[0018] For ease of understanding, the specific process of the embodiments of the present invention is described below. Please refer to [link / reference]. Figure 1 A flowchart of the manufacturing method of ultra-high temperature self-regulating electric heating cable provided in this embodiment of the invention is shown. The method specifically includes the following steps: The manufacturing method of ultra-high temperature self-regulating electric heating tape includes the following steps: S1. Preparation of composite conductive filler: PFA resin, composite conductive filler, nucleating agent and antioxidant are melt-blended and ultrasonically dispersed to obtain PTC core material. S2. The PTC core material, the first insulation layer material, and the outer sheath material are co-extruded in one step through a three-layer co-extrusion die head to form a preform. S3. The preform is subjected to gradient irradiation crosslinking, and the irradiated product is annealed and polarized. A metal shielding layer is set on the outside of the formed composite and external terminals are installed to obtain an ultra-high temperature self-regulating electric heating cable.
[0019] In this embodiment, the ultra-high temperature self-regulating electric heating cable includes a stranded nickel-plated copper conductor, a PTC heating core layer, a first insulating layer, a metal shielding layer, and an outer sheath layer. The PTC heating core layer adopts a PFA / hybrid carbon composite system. The conductive filler in the PFA / hybrid carbon composite system is a nanoparticle with a core-shell structure. The PTC heating core layer exhibits a gradient distribution of cross-linking degree along the radial direction, with the cross-linking degree of the surface layer being higher than that of the core layer. Specifically, the cross-linking degree of the surface layer is 85%–95%, and the cross-linking degree of the core layer is 60%–75%. The shell of the nanoparticle is an in-situ polymerized conductive polymer layer, which is a polydopamine layer or a conductive polyaniline layer, with a shell thickness of 5–15 nm.
[0020] Please see Figure 2 The flowchart of step S1 provided in this embodiment of the invention specifically includes the following process: S11. Select high-structure carbon black as the core material, place the carbon black in a plasma treatment chamber, and perform low-temperature plasma surface treatment under an oxygen or nitrogen atmosphere. The treatment power is 100-300W and the time is 5-15min. Introduce active groups on the surface of the carbon black, wherein the active groups are one of hydroxyl, carboxyl or amino groups. S12. Disperse the activated carbon black in a buffer solution containing dopamine or aniline monomers at a concentration of 2-10 g / L, and stir and polymerize at room temperature for 12-24 hours to form a conductive polymer shell. After polymerization, centrifuge, wash and vacuum dry to obtain a composite conductive filler with a core-shell structure. S13. Weigh the PFA resin, composite conductive filler, nucleating agent and antioxidant according to the weight parts, and put them into the mixer for premixing. Feed the premixed material into a twin-screw extruder. The blended melt is extruded through a die, cooled and granulated to obtain PTC core material particles.
[0021] Furthermore, the mixture contains 60-80 parts of PFA resin, 15-25 parts of composite conductive filler, 5-10 parts of nucleating agent, and 1-3 parts of antioxidant.
[0022] Furthermore, step S13 specifically includes the following processes: PFA resin, composite conductive filler, nucleating agent and antioxidant are put into a mixer and premixed at room temperature for 5 to 10 minutes at a speed of 500 to 800 rpm to make the components initially dispersed evenly. The premixed material is fed into the twin-screw extruder through a metering feeder. The screw speed is 300-500 rpm. The temperature of each section of the twin-screw extruder is set as follows: feeding section 320-340℃, melting section 350-370℃, mixing section 370-380℃, and die head temperature 360-370℃. After the melting section of the twin-screw extruder, an ultrasonic probe is inserted into the material melt. The ultrasonic frequency is 20-40kHz and the power is 500-1000W. Under the action of ultrasound, the core-shell structure filler is uniformly dispersed. The blended melt is extruded through a die, cooled, and granulated to obtain PTC core material particles.
[0023] Please see Figure 3 The flowchart of step S2 provided in this embodiment of the invention specifically includes the following processes: S21. A three-layer co-extrusion composite die head is used, and the inside of the die head adopts a split channel design so that the three layers of material converge in front of the exit die; S22. The stranded nickel-plated copper conductor passes through the center of the die head at a constant speed of 1-5 m / min under the action of the traction device. The first insulation layer covers the outside of the PTC core layer, and the outer sheath layer covers the outermost layer. After extrusion, it is cooled and shaped by the sizing sleeve and cooling water tank to form a blank.
[0024] Furthermore, the PTC core layer extruder temperature is 340–370°C, the first insulation layer extruder temperature is 350–380°C, the outer sheath layer extruder temperature is 350–380°C, and the co-extrusion die head temperature is 360–375°C. Furthermore, the extrusion speed of the PTC core layer extruder is 5-15 rpm, the extrusion speed of the first insulation layer extruder is 8-20 rpm, and the extrusion speed of the outer sheath layer extruder is 10-20 rpm; Furthermore, the first insulation layer material is PFA with high insulation resistance and high temperature resistance, and the outer sheath material is PFA with added UV-resistant and corrosion-resistant additives.
[0025] Please see Figure 4 The flowchart of step S3 provided in this embodiment of the invention includes the following specific processes: S31. Unwind the obtained preform on an unwinding device and irradiate it through the electron accelerator irradiation chamber at a speed of 1-3 m / min for the first stage of irradiation. The electron beam energy is 1.5-3.0 MeV, the beam current intensity is 20-50 mA, and the irradiation dose is 80-120 kG. S32. The preform after the first stage of irradiation is sent into the second irradiation chamber. A cobalt-60 gamma ray source is used, and the irradiation dose is 30-60 kGy. By the difference in the irradiation dose between the two stages, a gradient distribution of crosslinking degree is achieved in the radial direction from the core layer to the surface layer. S33. The irradiated preform is placed in a nitrogen-protected oven. After the composite is cooled, tin-plated copper wire or nickel-plated copper wire is braided into a metal shielding layer using a braiding machine. S34. Remove the outer sheath and insulation layer at both ends of the heating cable to expose the conductor, and install explosion-proof and waterproof external terminals by welding to obtain an ultra-high temperature self-regulating heating cable.
[0026] Furthermore, the oven temperature is increased to 200°C at a rate of 5°C / min and held for 1 hour, then increased to 240°C at a rate of 3°C / min and held for 1-2 hours, and finally cooled naturally to below 60°C before being removed from the oven.
[0027] The following detailed description of an ultra-high temperature self-regulating electric heating tape and its manufacturing method provided by the present invention, with reference to the embodiments, should not be construed as limiting the scope of protection of the present invention.
[0028] Example 1 Material composition: The matrix resin is perfluoroalkoxy resin (PFA) with a melt index of 5 g / 10min, and the amount used is 70 parts by weight; the composite conductive filler is core-shell structured nanoparticles, in which the core is high-structure carbon black with a DBP absorption value of 320 mL / 100 g and an average particle size of 50 nm, and the shell is an in-situ polymerized polydopamine layer with a shell thickness of 10 nm, and the amount used is 20 parts by weight; the nucleating agent is talc with an average particle size of 2 μm, and the amount used is 8 parts by weight; the antioxidant is hindered phenolic antioxidant 1010, and the amount used is 2 parts by weight.
[0029] Manufacturing process: S1. Preparation of composite conductive filler and mixing of PTC core material: Carbon black was placed in a plasma treatment chamber and subjected to low-temperature plasma surface treatment under an oxygen atmosphere. The atmosphere pressure was 30 Pa, the treatment power was 200 W, and the treatment time was 10 min. The activated carbon black was dispersed in a Tris-HCl buffer solution containing 5 g / L dopamine (pH 8.5). The solution was stirred and polymerized at room temperature for 18 hours. After polymerization, the carbon black was centrifuged, washed, and vacuum dried at 50°C for 12 hours to obtain a polydopamine-coated core-shell structure composite conductive filler. PFA resin, composite conductive filler, talc, and antioxidant 1010 were weighed according to the above weight proportions and added to a high-speed mixer. The mixture was premixed at 600 rpm for 8 min. The premixed material was fed into a twin-screw extruder with a length-to-diameter ratio of 44:1 for melt blending. The temperatures of each section of the extruder were set as follows: feeding section 330°C, melting section 360°C, mixing section 375°C, die head 365°C, and screw speed 400 rpm. rpm; An ultrasonic-assisted dispersion device is installed after the melting section of the twin-screw extruder. The ultrasonic frequency is 30 kHz and the power is 800 W to ensure uniform dispersion of the filler. The blended melt is extruded through a die, cooled, and granulated to obtain PTC core material particles. S2. Three-layer co-extrusion molding: Three single-screw extruders are configured to supply PTC core material, first insulation layer material (modified PFA), and outer sheath material (weather-resistant PFA), respectively. The PTC core extruder temperature is 350℃, the first insulation layer extruder temperature is 370℃, the outer sheath layer extruder temperature is 370℃, and the three-layer co-extrusion die head temperature is 365℃. The screw speeds of each extruder are: core layer 10 rpm, insulation layer 12 rpm, and sheath layer 15 rpm; the traction speed is 3 m / min. The stranded nickel-plated copper conductor is composed of 7 strands of 0.4 mm diameter nickel-plated copper wire, which pass through the center of the die head at a constant speed under the action of the traction device. The PTC core material tightly covers the conductor surface, the first insulation layer covers the outside of the PTC core layer, and the outer sheath layer covers the outermost layer. After extrusion, it is rapidly cooled and shaped in a 30℃ cooling water bath to form a preform. S3. Gradient Irradiation Crosslinking, Annealing Polarization, and Post-Assembly: The preform was irradiated for the first stage at a speed of 2 m / min through an electron accelerator irradiation chamber with an electron beam energy of 2.0 MeV, a beam current of 30 mA, and an irradiation dose of 100 kGy. Subsequently, the preform was sent to a cobalt-60 gamma-ray source irradiation chamber for the second stage of irradiation with an irradiation dose of 45 kGy. The two-stage irradiation achieved a radial crosslinking gradient distribution, with a surface crosslinking degree of 92% and a core crosslinking degree of 68%. The irradiated preform was then placed in a nitrogen-protected oven for annealing. The temperature was increased to 200℃ at a rate of 5℃ / min and held for 1 hour, then increased to 240℃ at a rate of 3℃ / min and held for 1.5 hours. Finally, it was allowed to cool naturally to below 60℃ before being removed from the oven. After cooling, a 16-spindle braiding machine was used to braid a 0.15 mm diameter... A metal shielding layer is formed by braiding tinned copper wire of mm with a braiding density of 85%. The outer sheath and insulation layer are removed at both ends of the heat tracing cable to expose the conductor. Explosion-proof external terminals are installed by crimping to obtain the finished product.
[0030] Product Performance: Testing showed that the ultra-high temperature self-regulating electric heating cable produced in this embodiment maintained a maximum temperature of 262℃ and had an extreme withstand temperature of 287℃. Its resistance at room temperature (25℃) was 12.5 Ω / m, and at 260℃ it was 21500 Ω / m, with a resistance change factor (R260 / R25) of 1.72 × 10⁻⁶. 3 The temperature control accuracy is ±4.5℃. After 10,000 hours of continuous operation at 260℃, the power attenuation rate is 12.8%. The insulation resistance is 150 MΩ, and it withstands a voltage of 2.5 kV for 1 minute without breakdown.
[0031] Example 2: Material composition: The matrix resin is perfluoroalkoxy resin (PFA) with a melt index of 3 g / 10min and a dosage of 65 parts by weight; the composite conductive filler is core-shell structured nanoparticles, with the core being high-structure carbon black with a DBP absorption value of 340 mL / 100g and an average particle size of 40 nm, and the shell being an in-situ polymerized conductive polyaniline layer with a shell thickness of 8 nm, and a dosage of 25 parts by weight; the nucleating agent is organophosphate nucleating agent TMP-6, with a dosage of 7 parts by weight; the antioxidant is phosphite antioxidant 168, with a dosage of 3 parts by weight.
[0032] Manufacturing process: S1. Preparation of Composite Conductive Filler and Mixing of PTC Core Material: Carbon black was placed in a plasma treatment chamber and subjected to low-temperature plasma surface treatment under a nitrogen atmosphere. The atmosphere pressure was 40 Pa, the treatment power was 250 W, and the treatment time was 8 min. The activated carbon black was dispersed in a hydrochloric acid solution containing aniline monomer at a concentration of 8 g / L and a pH of 3. Ammonium persulfate was added as an initiator, and the mixture was stirred and polymerized at room temperature for 24 hours. After polymerization, the mixture was centrifuged, washed, and dried to obtain a core-shell structured composite conductive filler coated with conductive polyaniline with a shell thickness of 8 nm. The components were weighed according to the above weight proportions and added to a high-speed mixer. The mixture was premixed at 700 rpm for 6 min. The premixed material was fed into a twin-screw extruder with a length-to-diameter ratio of 40:1 for melt blending. The extruder temperature was set as follows: feeding section 340℃, melting section 365℃, mixing section 380℃, die head 370℃, and screw speed 450 rpm. rpm; An ultrasonic-assisted dispersion device is installed in the middle section of a twin-screw extruder with an ultrasonic frequency of 40 kHz and a power of 700 W; after blending, the mixture is extruded and granulated to obtain PTC core material particles; S2. Three-layer co-extrusion molding: The extruder temperature for the PTC core layer is 360℃, the extruder temperature for the first insulation layer (modified PFA) is 375℃, the extruder temperature for the outer sheath layer (weather-resistant PFA) is 375℃, and the extruder head temperature for the three-layer co-extrusion is 370℃; the screw speeds of each extruder are: core layer 12 rpm, insulation layer 10 rpm, and sheath layer 12 rpm; the traction speed is 4 m / min; the stranded nickel-plated copper conductor is made of 19 strands of nickel-plated copper wire with a diameter of 0.3 mm; after the three-layer material is co-extruded in one step, it is cooled and shaped in a 25℃ cooling water bath to form a preform; S3. Gradient irradiation crosslinking, annealing polarization, and post-assembly: The first stage of irradiation uses an electron accelerator with an electron beam energy of 1.8 MeV, a beam current of 40 mA, an irradiation dose of 110 kGy, and a preform travel speed of 1.5 m / min; the second stage of irradiation uses a low-energy electron beam with an electron beam energy of 0.4 MeV and an irradiation dose of 50 kGy; after irradiation, the surface crosslinking degree of the preform is 90%, and the core crosslinking degree is 65%; the annealing treatment is carried out under nitrogen protection: first, it is held at 200℃ for 1 hour, then at 230℃ for 2 hours, and then naturally cooled; the metal shielding layer is wrapped by a 20 mm wide copper foil spirally wrapped around the surface of the composite, with an overlap rate of 30%; finally, external terminals are installed to obtain the finished product.
[0033] Product Performance: Testing showed that the ultra-high temperature self-regulating electric heating cable produced in this embodiment maintains a maximum temperature of 265℃ and has an ultimate withstand temperature of 290℃. Its resistance at room temperature (25℃) is 9.8 Ω / m, and at 260℃, it is 19800 Ω / m. The resistance change factor (R260 / R25) is 2.02 × 10⁻⁶. 3 The temperature control accuracy is ±4.0℃. After 10,000 hours of continuous operation at 260℃, the power attenuation rate is 10.5%. The insulation resistance is 180 MΩ, and it withstands a voltage of 2.5 kV for 1 minute without breakdown.
[0034] Example 3: Material composition: The matrix resin is perfluoroalkoxy resin (PFA) with a melt index of 8 g / 10min, and the dosage is 75 parts by weight; the composite conductive filler is core-shell structured nanoparticles, with the core being high-structure carbon black, DBP absorption value of 310 mL / 100g, average particle size of 60 nm, and the shell being an in-situ polymerized polydopamine layer with a shell thickness of 12 nm, and the dosage of the composite conductive filler is 18 parts by weight; the nucleating agent is modified nano-montmorillonite with an average particle size of 1 μm, and the dosage is 6 parts by weight; the antioxidant is a composite antioxidant, which is a mixture of hindered phenolic antioxidant 1010 and phosphite antioxidant 168 in a weight ratio of 1:1, and the total dosage is 1 part by weight.
[0035] Manufacturing process: S1. Preparation of composite conductive filler and mixing of PTC core material: Carbon black was placed in a plasma treatment chamber and treated under an oxygen atmosphere at a pressure of 25 Pa, a power of 150 W, and a time of 12 min. The activated carbon black was dispersed in a Tris-HCl buffer solution (pH=8.5) containing 3 g / L dopamine and polymerized at room temperature for 20 hours. After centrifugation, washing, and drying, a polydopamine-coated core-shell structure composite conductive filler with a shell thickness of 12 nm was obtained. The components were weighed according to the above weight proportions and added to a high-speed mixer for premixing at 500 rpm for 10 min. The premixed material was fed into a twin-screw extruder with a length-to-diameter ratio of 48:1. The temperatures were set as follows: feeding section 320℃, melting section 350℃, mixing section 370℃, die head 360℃, and screw speed 350 rpm. The ultrasonic-assisted dispersion frequency was 25 kHz and the power was 900 W. W; after blending, extrusion granulation is performed to obtain PTC core material particles; S2. Three-layer co-extrusion molding: The extruder temperature for the PTC core layer is 345℃, the extruder temperature for the first insulation layer (modified PFA) is 360℃, the extruder temperature for the outer sheath layer (weather-resistant PFA) is 360℃, and the co-extrusion die head temperature is 355℃; the screw speeds are: core layer 8 rpm, insulation layer 14 rpm, and sheath layer 18 rpm; the traction speed is 2.5 m / min; the stranded nickel-plated copper conductor is made of 7 strands of nickel-plated copper wire with a diameter of 0.5 mm; after extrusion, it is cooled and shaped in a 20℃ cooling water bath to form a preform; S3. Gradient irradiation crosslinking, annealing polarization, and post-assembly: The first stage of irradiation uses an electron accelerator with an electron beam energy of 2.5 MeV, a beam current of 25 mA, an irradiation dose of 85 kGy, and a preform travel speed of 2.5 m / min; the second stage of irradiation uses a cobalt-60 gamma ray source with an irradiation dose of 35 kGy; after irradiation, the surface crosslinking degree of the preform is 88%, and the core crosslinking degree is 62%; the annealing treatment is carried out under nitrogen protection: first, it is held at 200℃ for 1 hour, then at 220℃ for 2 hours, and then naturally cooled; the metal shielding layer is woven using a 24-spindle braiding machine to weave nickel-plated copper wire with a diameter of 0.1 mm to form the shielding layer, with a braiding density of 90%; finally, external terminals are installed to obtain the finished product.
[0036] Product Performance: Testing showed that the ultra-high temperature self-regulating electric heating cable produced in this embodiment maintains a maximum temperature of 260℃ and has an ultimate withstand temperature of 283℃. Its resistance at room temperature (25℃) is 15.2 Ω / m, and at 260℃ it is 24200 Ω / m, with a resistance change factor (R260 / R25) of 1.59 × 10⁻⁶. 3 The temperature control accuracy is ±5.0℃. After 10,000 hours of continuous operation at 260℃, the power attenuation rate is 14.2%. The insulation resistance is 130 MΩ, and it withstands a voltage of 2.5 kV for 1 minute without breakdown.
[0037] In this embodiment of the invention, a modified PFA / hybrid carbon composite system is used as the PTC heating core material. The PFA resin exhibits excellent thermal stability, and when combined with a core-shell structured conductive filler, it effectively suppresses filler agglomeration and interfacial slippage at high temperatures. Through gradient irradiation crosslinking technology, the surface layer of the heating core achieves a high degree of crosslinking of 85%–95%, while the core layer maintains a moderate degree of crosslinking of 60%–75%. This endows the product with the ability to operate stably for extended periods at extreme temperatures of 260°C and above. The core-shell structure design optimizes the interfacial bonding between the conductive filler and the polymer matrix. Combined with annealing polarization treatment, the conductive network can respond rapidly and generate a significant resistance jump when the temperature rises. This ensures that the heating cable automatically reduces its output power after reaching the set temperature, avoiding localized overheating and significantly improving the safety and reliability of the heating system. Employing a gradient irradiation crosslinking structure, the high degree of crosslinking in the surface layer provides excellent resistance to thermal oxidation and creep, while moderate crosslinking in the core layer preserves the stability of the PTC effect. Ultrasonic-assisted dispersion ensures the uniform distribution of the core-shell filler in the matrix, significantly extending its service life and reducing maintenance and replacement costs. The core-shell structure conductive filler is prepared by combining plasma surface treatment with in-situ polymerization, ensuring the stability and repeatability of the filler structure. Ultrasonic-assisted melt blending significantly improves the uniformity of filler dispersion and avoids agglomeration defects caused by traditional mechanical stirring. Three-layer co-extrusion in a single molding process achieves a tight bond between the core layer, insulation layer, and sheath layer, eliminating interlayer interface defects.
[0038] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely preferred examples and are not intended to limit the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of the present invention is defined by the appended claims and their equivalents.
Claims
1. A high-temperature self-regulating electric heating tape and its manufacturing method, characterized in that, The ultra-high temperature self-regulating electric heating cable includes a stranded nickel-plated copper conductor, a PTC heating core layer, a first insulation layer, a metal shielding layer, and an outer sheath layer; The manufacturing method of ultra-high temperature self-regulating electric heating tape includes the following steps: S1. Preparation of composite conductive filler: PFA resin, composite conductive filler, nucleating agent and antioxidant are melt-blended and ultrasonically dispersed to obtain PTC core material. S2. The PTC core material, the first insulation layer material, and the outer sheath material are co-extruded in one step through a three-layer co-extrusion die head to form a preform. S3. The preform is subjected to gradient irradiation crosslinking, and the irradiated product is annealed and polarized. A metal shielding layer is set on the outside of the formed composite and external terminals are installed to obtain an ultra-high temperature self-regulating electric heating cable.
2. The ultra-high temperature self-regulating electric heating tape as described in claim 1, characterized in that, The PTC heating core layer adopts a PFA / hybrid carbon composite system. The conductive filler in the PFA / hybrid carbon composite system is a nanoparticle with a core-shell structure. The PTC heating core layer exhibits a gradient distribution of crosslinking degree along the radial direction, with the crosslinking degree of the surface layer being higher than that of the core layer. Specifically, the crosslinking degree of the surface layer is 85% to 95%, and the crosslinking degree of the core layer is 60% to 75%.
3. The ultra-high temperature self-regulating electric heating tape and its manufacturing method as described in claim 1, characterized in that, The shell of the nanoparticles is an in-situ polymerized conductive polymer layer, which is a polydopamine layer or a conductive polyaniline layer, with a shell thickness of 5–15 nm.
4. The ultra-high temperature self-regulating electric heating tape and its manufacturing method as described in claim 1, characterized in that, Step S1 details Includes the following processes: S11. Select high-structure carbon black as the core material, place the carbon black in a plasma treatment chamber, and perform low-temperature plasma surface treatment under an oxygen or nitrogen atmosphere. The treatment power is 100-300W and the time is 5-15min. Introduce active groups on the surface of the carbon black, wherein the active groups are one of hydroxyl, carboxyl or amino groups. S12. Disperse the activated carbon black in a buffer solution containing dopamine or aniline monomers at a concentration of 2-10 g / L, and stir and polymerize at room temperature for 12-24 hours to form a conductive polymer shell. After polymerization, centrifuge, wash and vacuum dry to obtain a composite conductive filler with a core-shell structure. S13. Weigh the PFA resin, composite conductive filler, nucleating agent and antioxidant according to the weight parts, and put them into the mixer for premixing. Feed the premixed material into a twin-screw extruder. The blended melt is extruded through a die, cooled and granulated to obtain PTC core material particles.
5. The ultra-high temperature self-regulating electric heating tape and its manufacturing method as described in claim 4, characterized in that, 60-80 parts PFA resin, 15-25 parts composite conductive filler, 5-10 parts nucleating agent, and 1-3 parts antioxidant.
6. The ultra-high temperature self-regulating electric heating tape and its manufacturing method as described in claim 4, characterized in that, Step S13 specifically includes the following processes: PFA resin, composite conductive filler, nucleating agent and antioxidant are put into a mixer and premixed at room temperature for 5 to 10 minutes at a speed of 500 to 800 rpm to make the components initially dispersed evenly. The premixed material is fed into the twin-screw extruder through a metering feeder. The screw speed is 300-500 rpm. The temperature of each section of the twin-screw extruder is set as follows: feeding section 320-340℃, melting section 350-370℃, mixing section 370-380℃, and die head temperature 360-370℃. After the melting section of the twin-screw extruder, an ultrasonic probe is inserted into the material melt. The ultrasonic frequency is 20-40 kHz and the power is 500-1000 W. Under the action of ultrasound, the core-shell structure filler is uniformly dispersed. The blended melt is extruded through a die, cooled, and granulated to obtain PTC core material particles.
7. The ultra-high temperature self-regulating electric heating tape and its manufacturing method as described in claim 1, characterized in that, Step S2 specifically includes the following processes: S21. A three-layer co-extrusion composite die head is used, and the inside of the die head adopts a split channel design so that the three layers of material converge in front of the exit die; The extruder temperature for the PTC core layer is 340–370℃, the extruder temperature for the first insulation layer is 350–380℃, the extruder temperature for the outer sheath layer is 350–380℃, and the co-extrusion die head temperature is 360–375℃. The extrusion speed of the PTC core layer extruder is 5-15 rpm, the extrusion speed of the first insulation layer extruder is 8-20 rpm, and the extrusion speed of the outer sheath layer extruder is 10-20 rpm. S22. The stranded nickel-plated copper conductor passes through the center of the die head at a constant speed of 1-5 m / min under the action of the traction device. The first insulation layer covers the outside of the PTC core layer, and the outer sheath layer covers the outermost layer. After extrusion, it is cooled and shaped by the sizing sleeve and cooling water tank to form a blank.
8. The ultra-high temperature self-regulating electric heating tape and its manufacturing method as described in claim 7, characterized in that, The first insulating layer material is PFA with high insulation resistance and high temperature resistance, and the outer sheath material is PFA with added UV-resistant and corrosion-resistant additives.
9. The ultra-high temperature self-regulating electric heating tape and its manufacturing method as described in claim 1, characterized in that, Step S3 details Includes the following processes: S31. Unwind the obtained preform on an unwinding device and irradiate it through the electron accelerator irradiation chamber at a speed of 1-3 m / min for the first stage of irradiation. The electron beam energy is 1.5-3.0 MeV, the beam current intensity is 20-50 mA, and the irradiation dose is 80-120 kG. S32. The preform after the first stage of irradiation is sent into the second irradiation chamber. A cobalt-60 gamma ray source is used, and the irradiation dose is 30-60 kGy. By the difference in the irradiation dose between the two stages, a gradient distribution of crosslinking degree is achieved in the radial direction from the core layer to the surface layer. S33. The irradiated preform is placed in a nitrogen-protected oven. After the composite is cooled, tin-plated copper wire or nickel-plated copper wire is braided into a metal shielding layer using a braiding machine. S34. Remove the outer sheath and insulation layer at both ends of the heating cable to expose the conductor, and install explosion-proof and waterproof external terminals by welding to obtain an ultra-high temperature self-regulating heating cable.
10. The ultra-high temperature self-regulating electric heating tape and its manufacturing method as described in claim 1, characterized in that, The oven is heated to 200°C at a rate of 5°C / min and held for 1 hour. Then, the temperature is increased to 240°C at a rate of 3°C / min and held for 1 to 2 hours. Finally, the oven is allowed to cool naturally to below 60°C before being removed from the oven.